Faktor Penyebab Prokrastinasi Akademik Penyusunan Skripsi pada Mahasiswa FIP UNNES - Fitriah, Zahratul; Kurniawan, Kusnarto; Sri Hartati, Maria Theresia (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This study was conducted based on the phenomena that occurs in the Faculty of Education UNNES that 58% of students class of 2009 FIP UNNES still not complete his studies on the 9th semester, though they should have completed their studies. This study aim to know the causes of academic procrastination thesis preparation on the subject of research. This research is a descriptive survey. Data collection method using the questionnaire in the form of psychological scale. The result showed that the causes of academic procrastination thesis preparation at the Faculty of  Education students Unnes class of 2009 is, motivation 83%, doing other things more fun 79%, lack of assertiveness  79%, dislike of duty 78%, dreamer 75%, anxiety 73%, stress 73%, deffender 74%,  over doer 74%,  time management issue 72%, crisis maker 71%, fear of failure 71%, enjoy working under preasure 71%, self-depreciation 70%, hostility with other 70%, low discomfort tolerance 68%, poor task aproach  66%, perfectionisme 66%, parenting parents 76%, lecturers problems 73%, the bureaucracy complicated  73%, learning environment issue 63% and administrative services 55%